2018
DOI: 10.1108/jedt-06-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of building information modelling adoption among quantity surveyors in Ghana

Abstract: Purpose -The purpose of this paper is to empirically study the factors that facilitate adoption of building information modelling (BIM) among quantity surveyors (QSs) using the unified theory of acceptance and use of technology (UTAUT).Design/methodology/approach -Using a quantitative approach, factors identified in the UTAUT are examined. The empirical investigation has been conducted using survey questionnaire. The data set has been obtained from 73 practicing QSs in Ghana.Findings -The results indicated a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
(61 reference statements)
1
19
2
Order By: Relevance
“…On the individual level, Unified theory of acceptance and use of technology (UTAUT) is usually employed for BIM adoption. Addy et al [26] studied factors affecting BIM adoption for quantity surveyors in Ghana with UTAUT; Howard et al [27] added the variable of attitude and employs moderators of experience and voluntariness to UTAUT. Empirical study indicated that BIM was perceived as an unrewarded addition to existing work processes.…”
Section: Bim Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the individual level, Unified theory of acceptance and use of technology (UTAUT) is usually employed for BIM adoption. Addy et al [26] studied factors affecting BIM adoption for quantity surveyors in Ghana with UTAUT; Howard et al [27] added the variable of attitude and employs moderators of experience and voluntariness to UTAUT. Empirical study indicated that BIM was perceived as an unrewarded addition to existing work processes.…”
Section: Bim Adoptionmentioning
confidence: 99%
“…This conclusion is consistent with Dossick's [63] conclusion that information technology adoption in the construction industry depends on personal leadership. Further, Won [26] concluded that the interest and willingness of project managers are the most important success factors in BIM adoption. Especially in AEC organizations in China, a leader always has administrative Corporate/project leadership and software functionality are two fundamental factors affecting BIM adoption in AEC organizations.…”
Section: Hierarchical Analysismentioning
confidence: 99%
“…More so, the higher levels of BIM awareness in Nigeria do not necessarily translate into implementation (Saka and Chan, 2019c). On the other hand, other studies including (Gamil and Rahman, 2019;Addy et al, 2018;Olawumi and Chan, 2019b) have highlighted the importance of awareness of BIM, and need for investigating the barriers, and antecedents in developing countries, and development of benchmarking model that will enhance BIM. However, there is limited knowledge on the barriers to implementation of building information modelling (BIM) within the Nigerian construction industry, viewed from the construction professional's lenses.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important adoption models accepted by technology adoption scholars is the Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al, 2003). The model has been applied to investigate BIM adoption in several contexts such as the United Kingdom (Davies and Harty, 2013;Howard et al, 2017), Ghana (Addy et al, 2018), Australia (Sargent et al, 2012), and Peru (Murguia, Demian, et al, 2021). However, it is recognised that UTAUT neglects the broader institutional context in which the information technology is deployed.…”
Section: Introductionmentioning
confidence: 99%